The Interpersonal Meaning In Prince Charles III Grief Speech - Andini Syita Savitri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study refers to analyzing language called for communication. It fully focuses on Prince Charles III delivers Queen’s speech from the perspective of SFL especially dealing with the Tenor of the discourse of the speech. In other words, this object is about interpersonal meaning of the speech that is able to be used to discuss speaker’s posture towards what s/he is delivering in the speech. In conducting this study, it has two objectives to achieve. First, this study tried to figure the interpersonal meaning of Prince Charles III speech by looking deeply on the Mood system of the sentence of the speech which indicates analyzing the two constituents of Mood are Subjects and Finites of the clauses in the speech. Second, it also tried to unbox Charles posture towards his people by applying the Appraisal theory proposed by Martin. Appraisal offers an ideal analytical framework to frequently identify interpersonal meanings in language. The result of this study showed that the most subject found in the speech was I – Prince Charles meant that Charles himself was aware to what he was preaching in the speech. The Finites in the speech were primarily stapulated in Simple Present Tense that was emphasized that in giving his speech, Charles gave the general truth at the moment of the speaking. Since nearly all of the clauses were declarative clauses, Charles was considered to share information in this case he shared how much he loves his mother who just passed away and how she become a role model to him to be a great sovereign. That shared information was further analyzed with the Appraisal theory which tent to the conclusion that Charles in deeply lost someone who is important in his life. Based on this study, finally it comes to an understanding that it is important to understand any kinds of speech well. One among paths to do it is by analyzing that speech through its interpersonal meaning and its appraisal system. This study is beneficial for readers, especially English Department students in order to get able to figure the meaning behind a text well.